2014
DOI: 10.1128/aac.02788-14
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Daclatasvir Resistance Barriers on NS5A from Hepatitis C Virus Genotypes 1 to 6: Implications for Cross-Genotype Activity

Abstract: A comparison of the daclatasvir (DCV [BMS-790052]) resistance barrier on authentic or hybrid replicons containing NS5A from hepatitis C virus (HCV) genotypes 1 to 6 (GT-1 to -6) was completed using a replicon elimination assay. The data indicated that genotype 1b (GT-1b) has the highest relative resistance barrier and genotype 2a (GT-2a M31) has the lowest. The rank order of resistance barriers to DCV was 1b > 4a > 5a > 6a Х 1a > 2a JFH > 3a > 2a M31. Importantly, DCV in combination with a protease inhibitor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…DCV alone (250 nM) is efficient for replicon elimination on gts 4a, 5a, and 6a. The ability of DCV to eliminate replicons in this assay format (4a Х 5a Ͼ 6a Ͼ 1a Ͼ 3a Х 2a NIH) is in agreement with the results from previous experiments (3). Syn-690 alone (150 nM) appears most active on gt 3a but has poor activity overall.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…DCV alone (250 nM) is efficient for replicon elimination on gts 4a, 5a, and 6a. The ability of DCV to eliminate replicons in this assay format (4a Х 5a Ͼ 6a Ͼ 1a Ͼ 3a Х 2a NIH) is in agreement with the results from previous experiments (3). Syn-690 alone (150 nM) appears most active on gt 3a but has poor activity overall.…”
Section: Resultssupporting
confidence: 81%
“…NS5A-Syn activity enhances the pangenotype coverage of DCV. Colony elimination studies have been used to determine the relative resistance barrier of DCV on multiple genotypes: 1b Ͼ 4a Ն 5a Ͼ 6a Х 1a Ͼ 2a JFH Ͼ 3a Ͼ 2a NIH (3,25,26). DCV combined with a protease inhibitor (MK-5172) effectively eliminated the genotype with the lowest barrier to resistance (2a NIH), indicating that DCV used in combination with other DAAs can be highly effective on all genotypes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hezode et al (2014) reported that patients with CC IL28B genotype had a higher chance of achieving SVR, compared to those with a non-CC genotype, regardless of therapy . Also, as shown by in vivo and in vitro studies, the combination of L30 polymorphism and IL28B non-CC genotype can significantly increase daclatasvir resistance (Wang et al, 2012;Wang et al, 2014).…”
mentioning
confidence: 99%